1994
DOI: 10.1111/j.1748-0361.1994.tb00226.x
|View full text |Cite
|
Sign up to set email alerts
|

Health and Well‐Being of Childbearing Women in Rural and Urban Contexts

Abstract: As part of the national focus on women's health issues, it is important to identify those health-related characteristics of rural women that distinguish them from women living in urban settings. The aim of this study was to compare rural and urban childbearing women on socioeconomic characteristics, perceived stress, health-related practices, illness symptoms, parenting confidence, and body weight. One hundred sixty-five midwestern women responded to a health survey sent to them six months after childbirth. Ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Unwanted pregnancy can be a stressful experience for any woman [22], but being denied an abortion may exacerbate stress, making a woman feel disempowered or unable to cope with the stressor [11,45]. Preparing to carry an unwanted pregnancy to term, managing pregnancy itself, and potentially searching for another abortion provider may also contribute to stress [45].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unwanted pregnancy can be a stressful experience for any woman [22], but being denied an abortion may exacerbate stress, making a woman feel disempowered or unable to cope with the stressor [11,45]. Preparing to carry an unwanted pregnancy to term, managing pregnancy itself, and potentially searching for another abortion provider may also contribute to stress [45].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on stress and pregnancy provides little insight into the outcomes after unwanted pregnancy over time, as few studies compare parents and non-parents [22] and most do not consider the wantedness of the pregnancy [48]. However, early motherhood is a stressful period [49], perhaps more so if the baby is the result of an unwanted pregnancy [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, studies of women's health and mental health show that both are adversely affected by food insecurity (Siefert et al 2004;Walker et al 1994) while other research confirms the relationship of food insufficiency to depression and other poor health outcomes (Wu and Schimmele 2005;Vozoris and Tarasuk 2003;Tarasuk and Maclean 1990). Adding to recent research on American Indian populations (Bliss 2004;Pickering 2000;Ward and Whiting 2006;Whiting et al 2005), our recent analyses (Whiting and Ward 2007) support Wu and Schimmele's (2005) findings that food insufficiency is an important independent source of stress in low-income, minority populations.…”
Section: Introductionmentioning
confidence: 93%
“…Instead, it seems to have been assumed that people know what to do and have the ability and resources to carry out the necessary behaviors. 26,27 Rural environments also have fewer health care providers and less access to advanced medical technologies and information. Becker, Stuifbergen, and Sands found that among persons with disabilities, higher scores on a measure of barriers to health-promoting activities were negatively associated with general self-efficacy (r=-.48), perceived health status (r=-.29), and the likelihood of engaging in health-promoting behaviors (r=-.29).…”
Section: Approximately 350 000 Persons In the Unitedmentioning
confidence: 99%